Need equality and access equity to assistive products across genders and locations in 29 countries: a cross-sectional study - Borg, Johan; Muller, Sébastien; Eide, Arne H.; de Witte, Luc; Calvo, Irene; Khasnabis, Chapal; Zhang, Wei (Frontiers in Public Health, 2025)
BackgroundEvidence from nationally representative assistive product studies on needs equality and access equity is essential for effectively targeting measures by health and other services to improve access to assistive products. This multi-country study explored equality regarding the need for and equity regarding access to assistive products across genders and locations.Materials and methodsThis cross-sectional study analyzed aggregated self-reported data from 24 nationally and five sub-nationally representative surveys in countries with Human Development Index (HDI) ranging from 0.452 to 0.945. In 27 surveys, participants of all ages had been recruited through two-stage cluster sampling, while in two surveys participants aged 18 and above were recruited through simple random sampling. Individual-level data were collected through the Rapid Assistive Technology Assessment (rATA) questionnaire using personal, telephone, or web interviewing in 2019–2021. The main outcomes were assistive product needs inequality and access inequity, defined as the ratio of the difference in need or access between two sub-populations to the need or access in the total population.ResultsData were collected from 323,647 individuals of whom 44.9%−57.2% were women and 10.1%−89.5% lived in rural locations across the countries. Although varying considerably between countries, the need for assistive products including spectacles was generally higher among women while access was lower in rural areas and among women. Excluding spectacles, the need was higher and the access was lower in rural areas and among women. The access inequity between rural and urban areas was large (26% of the median access including spectacles, and 42% excluding spectacles) while it was smaller between women and men (6.4% including and 13% excluding spectacles). Access inequity decreased with increasing HDI.ConclusionIn efforts to achieve universal access to assistive products, especially location but also gender ought to be considered.